Integrating Anti-Corruption Values into Basic Mathematics Learning - Apriyani, Rini; Mulyati, Tita; Dewi, Dinie Anggraeni (International Conference on Elementary Education, 2025)
Elementary education plays a strategic role in shaping students' character and integrity. One important effort in this regard is the integration of anti-corruption values into the learning process, including mathematics learning. This study aims to describe the forms and strategies for integrating anti-corruption values into mathematics learning at the elementary school level. Using a qualitative descriptive approach through literature analysis and classroom-based contextual practice, this study identifies mathematics learning as an effective medium for fostering honesty, responsibility, and transparency among students. The research findings indicate that mathematics learning thatemphasizes logical reasoning, transparent group work, and problem-solving in a social context can foster anti-corruption awareness from an early age. The implementation of projects such as “classroom financial transparency” and integrity-based assessments encourage students to develop habits of honesty and fairness. Therefore, the integration of anti-corruption values into mathematics education not only improves students' numeracy skills but also contributes to building an integrity-based culture as the foundation of national character.